ATH-1105, a small-molecule positive modulator of the neurotrophic HGF system, is neuroprotective, preserves neuromotor function, and extends survival in preclinical models of ALS - Berthiaume, Andrée-Anne; Reda, Sherif M.; Kleist, Kayla N.; Setti, Sharay E.; Wu, Wei; Johnston, Jewel L.; Taylor, Robert W.; Stein, Liana R.; Moebius, Hans J.; Church, Kevin J. (Frontiers in Neuroscience, 2024)
Amyotrophic lateral sclerosis (ALS), a rapidly progressing and fatal neurodegenerative disorder, primarily affects the motor neurons of the brain and spinal cord. Like other neurodegenerative conditions, the neuron death central to disease progression is exacerbated by ongoing pathological processes such as increased inflammation, excitotoxicity, and protein accumulation.Hepatocyte growth factor (HGF) signaling through the MET receptor promotes a range of prosurvival, anti-apoptotic, and anti-inflammatory effects in multiple cell types, including the neurons and support cells of the nervous system. This pleiotropic system is therefore a potential therapeutic target for treatment of complex neurodegenerative disorders such as ALS. Here, we test the effects of ATH-1105, a small-molecule positive modulator of the HGF signaling system, in preclinical models of ALS. In vitro, MET, extracellular signal-regulated kinase (ERK), and protein kinase B (AKT) phosphorylation assays showed that ATH-1105 augments HGFmediated signaling. ATH-1105 protected primary cortical neurons from several neurotoxic insults and attenuated glutamate-mediated excitotoxicity in primary motor neurons. The antiinflammatory effects of ATH-1105 were seen in microglia-and macrophage-like cell systems exposed to lipopolysaccharide (LPS). ATH-1105 also mitigated the effects of glutamate excitotoxicity on motor neurons and astrocytes in cocultures. In a model of rat motor neurons cocultured with human muscle, treatment with ATH-1105 also had protective effects on motor neurons and neuromuscular junctions. In vivo, the impact of daily oral treatment with ATH-1105 from 1 to 3 months of age was evaluated in Prp-TDP-43 A315T hemizygous transgenic ALS mice. ATH-1105 treatment resulted in improved motor and nerve function, sciatic nerve axon and myelin integrity, and overall survival. Treatment with ATH-1105 also led to favorable reductions 3 in levels of plasma biomarkers of inflammation and neurodegeneration, along with decreased pathological protein accumulation (phospho-TDP-43) in the sciatic nerve. Additionally, both early intervention (treatment initiation at 1 month of age) and delayed intervention (treatment initiation at 2 months of age) with ATH-1105 produced benefits in this preclinical model of ALS. The consistent neuroprotective and anti-inflammatory effects demonstrated by ATH-1105 preclinically provide a compelling rationale for development of therapeutic interventions that leverage the positive modulation of the HGF pathway as a treatment for ALS.